Students' Metacognitive Strategies in Science Learning: A Case Study in Elementary Schools - Yuliana Wahyu; Kanisius Supardi; Gabariela Purnama Ningsi (MIMBAR PGSD Undiksha, 2025)
One of the essential skills that needs to be developed in science learning is metacognition, which refers to students’ ability to be aware of, monitor, and direct their own thinking processes through the stages of planning, monitoring, evaluating, and reflecting during the learning process. However, in practice, current science learning has not been optimal in stimulating students’ metacognitive skills, as learning activities tend to focus more on conceptual mastery rather than on developing thinking awareness. This study aims to analyze the metacognitive strategies employed by fifth-grade students in science learning, encompassing those four aspects. Using a qualitative approach with a case study design, this research explores students’ learning experiences in depth. Data were collected through observation, interviews, and document analysis, and analyzed using thematic analysis to identify emerging patterns of metacognitive strategies. The findings indicate that students’ metacognitive abilities in planning and monitoring are still very low, while in evaluation, some students began to review the material but were not yet consistent in evaluating their learning strategies. In terms of reflection, both teachers and students demonstrated a moderate category. Overall, the results emphasize the importance of explicitly integrating metacognitive strategies into science learning to foster students’ learning awareness and independence.